If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + y = 3 Solving -8x + y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -8x + y + -1y = 3 + -1y Combine like terms: y + -1y = 0 -8x + 0 = 3 + -1y -8x = 3 + -1y Divide each side by '-8'. x = -0.375 + 0.125y Simplifying x = -0.375 + 0.125y
| 5x+2*3x-1= | | -302=-5(4+8r)-2 | | 2n-2+2n-4=5 | | 5v+23=-2 | | 4x-8=2ax-2b | | 7/3(-16)-12= | | 5.5(-3*7.5)= | | x-0.13x= | | 3(7)+7y=84 | | -8(x+9)+8=-64 | | Y+8+y=5+2(y-6) | | 14x^3+35x-7x=0 | | 2u+8=-18 | | 2/3(-16)+4= | | 8x+11=14x-1 | | -15-2y=18 | | -12=2+2v+5v | | 9t+11=11 | | -40=8+-6s | | 3x+7(0)=84 | | 2(2x-5)=3(x-5)+4(2x-3) | | -24-2y=18 | | 3(0)+7y=84 | | 3(-13+1)=2(-13-5) | | 3.9=n+8.3-2.9 | | 5y+o=51 | | 4d-6=9d+2 | | x^2+x+-20=0 | | 2s+18=0 | | 8x+24x^3= | | -4.3x+3.2x=-3.52 | | 15-4n+3=2(3n-8)-9n |